Contextualized Teaching & Learning as a Fundamental Educational Model - Massimiliano Stramaglia; Rosita Deluigi; Laura Fedeli (Firenze University Press, 2018)
This paper aims to offer a scientific contribution to the clarification of some of the final training objectives that need to be achieved by a professional educator in reference to the relational and situational dynamics of the different educational contexts. Starting from a critical examination of the explicit skills that a university teacher in pedagogy (the primary professional model for the students of the L-19 Graduation Class) needs to have, the narrative approach in the acquisition of "embodied" knowledge is recognized as the possibility of training professionals able to perceive the totality of the educational mission and the specific research attitude that can surely connote the expert in educational processes.   La relazione didattica "in contesto" come paradigma educativo fondamentale L'articolo si propone di offrire un contributo scientifico alla delucidazione di alcuni degli obiettivi formativi finali che necessitano di essere conseguiti dall'educatore professionale socio-pedagogico in ordine alle dinamiche relazionali e situazionali specifiche dei diversi contesti educativi e formativi. A partire da una disamina critica delle competenze esplicite del docente universitario di pedagogia, modello primario di riferimento professionale per gli studenti della Classe delle Lauree L-19, si ravvisa nella trasmissione narrante di saperi "incarnati" la possibilità di formare professionisti in grado di percepire la globalità del mandato educativo e lo specifico atteggiamento di ricerca che non può che connotare l'esperto di processi educativi.